2010
DOI: 10.1128/aem.01525-09
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Diversity of Rhodopirellula Isolates from European Seas by Multilocus Sequence Analysis

Abstract: In the biogeography of microorganisms, the habitat size of an attached-living bacterium has never been investigated. We approached this theme with a multilocus sequence analysis (MLSA) study of new strains of Rhodopirellula sp., an attached-living planctomycete. The development of an MLSA for Rhodopirellula baltica enabled the characterization of the genetic diversity at the species level, beyond the resolution of the 16S rRNA gene. The alleles of the nine housekeeping genes acsA, guaA, trpE, purH, glpF, fumC,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 44 publications
3
22
1
Order By: Relevance
“…collected in Foz, Porto (Lage and Bondoso 2011). R. baltica is a cosmopolitan species of Planctomycetes as confirmed by 16S rRNA gene sequence analysis, DNA-DNA hybridization, and MLSA analysis (Schlesner et al 2004;Winkelmann et al 2010). It was found for the first time as a free-living organism in the water column in the Baltic Sea (Schlesner 1994) and, posteriorly, in the tissue of the Mediterranean sponge Intraspecies variability was accessed with the ERIC-PCR fingerprinting (Fig.…”
Section: Molecular Identification By 16s Rdna and Eric Fingerprintingmentioning
confidence: 99%
“…collected in Foz, Porto (Lage and Bondoso 2011). R. baltica is a cosmopolitan species of Planctomycetes as confirmed by 16S rRNA gene sequence analysis, DNA-DNA hybridization, and MLSA analysis (Schlesner et al 2004;Winkelmann et al 2010). It was found for the first time as a free-living organism in the water column in the Baltic Sea (Schlesner 1994) and, posteriorly, in the tissue of the Mediterranean sponge Intraspecies variability was accessed with the ERIC-PCR fingerprinting (Fig.…”
Section: Molecular Identification By 16s Rdna and Eric Fingerprintingmentioning
confidence: 99%
“…A systematic isolation resulted in a strain collection of the genus Rhodopirellula from European coastal seas and sediments, with many strains affiliating according to 16S rRNA gene sequence identity of 99.5-100% to R. baltica SH1 T (Winkelmann and Harder, 2009). However, a multilocus sequence analysis and DNA-DNA hybridization experiments revealed the presence of several species (Winkelmann et al, 2010). This observation was confirmed by draft genome sequences: the average nucleotide identity of shared genes between the strains revealed three species; R. baltica (strains SH1 T , SH28, WH47, SWK14 ), 'R.…”
Section: Introductionmentioning
confidence: 56%
“…europaea' and 'R. islandica' were found only in the samples from the regions where Winkelmann et al (2010) had isolated the strains and which had been suggested as a preferable habitat. However, as we found these species in almost all samples it is likely that upon favorable change in the environment they could become abundant in other regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations